I'm in the process of minimizing a boolean equation, and I've gotten it into the following form:

$$\lnot B \lor (B \land \lnot C) \lor C$$

Just by looking at it, I can tell that this is always TRUE. The complements of the center term are covered by the other two. However, I can't quite prove it formally.

I can split the middle term using indempotency:

$$\lnot B \lor (B \land \lnot C) \lor (B \land \lnot C) \lor C$$

Then (again, intuitively) I can tell that the two left terms simplify to: $\lnot B \land \lnot C$

What is the rule (or rules) that can get the left two terms into this form? Once I know that rule, I can formally solve the equation like so:

$$ \lnot B \lor \lnot C \lor C\lor B$$ $$(\lnot B \lor B) \lor (\lnot C \lor C)$$ $$ 1$$

Any help would be greatly appreciated!


$$\lnot B \lor (B \land \lnot C) \lor C$$ rearrange $$(\lnot B \lor C) \lor (B \land \lnot C)$$

Let's apply the De Morgan rule here quick:

$$(\lnot B \lor C) \lor \lnot(\lnot B \lor C)$$

I think it is called the "law of excluded middle" that $ A\lor \lnot A$ is always true, and that's what you have here for $ A = (\lnot B \lor C) $.

  • $\begingroup$ Aha! This is the nice, simple answer I was looking for. Thanks for the clarification :) $\endgroup$ – BraedenP Jan 27 '13 at 4:28
  • $\begingroup$ Sorry I deleted my previous comment which said "please accept". And of course it's ok if the other never got a good answer. $\endgroup$ – chx Jan 27 '13 at 4:34

$$\lnot B \lor (B \land \lnot C) \lor C$$ $$(\lnot B \lor B) \land (\lnot B \lor\lnot C) \lor C$$ $$T \land (\lnot B \lor\lnot C) \lor C$$ $$(\lnot B \lor\lnot C) \lor C$$ $$\lnot B \lor (\lnot C \lor C)$$ $$\lnot B \lor T$$ $$T$$


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.